PERAN MONUMEN TIROSA TERHADAP PENINGKATAN PENDAPATAN UMKM - Watudesi, Alfonzo Rodrigues; Gandur, Afrandi Sugiardi; Geong, Benediktus Maurisko; Pranto, Herodias Ardi; Lian, Yohanes Pemandi (JURNAL ADMINISTRASI KANTOR; Vol 12 No 2 (2024): Jurnal Administrasi Kantor (Desember 2024), 2024)
This article discusses the role of the TIROSA Monument in enhancing the income of Micro, Small, and Medium Enterprises (MSMEs) in KUPANG City, East Nusa Tenggara. Located in the city center, the monument serves as a strategic tourist attraction. The research employs a qualitative approach with a descriptive method, involving interviews and observations. The results indicate that while the TIROSA Monument has significant potential, challenges such as inadequate supporting facilities and cleanliness affect visitors’ interest. Recommendations are provided to improve facilities and foster collaboration among the government, community, and MSME actors to optimize tourism potential.   Keywords: TIROSA Monument, MSMEs, Tourism, Income, Facilities